Self-sustaining or sustaining cooperation? How Europe can ensure access to semiconductor technologies - Nina Czernich; Oliver Falck (EconPol Forum, 2026)
R&D in the semiconductor industry is concentrated in a few countries: Japan, Korea, China, the United States, and Taiwan. European countries' R&D cooperation centers around Europe and the US, with relatively little cooperation with Asia. Diversifying R&D partnerships may secure access to R&D hubs and key technologies. Policymakers can strengthen diversification by establishing adequate framework conditions. Focusing on Europe's comparative advantages can give it a competitive edge and greater bargaining power in global value chains.
Keywords: 330